2016
DOI: 10.1007/s00535-016-1235-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum Mac-2 binding protein glycosylation isomer predicts grade F4 liver fibrosis in patients with biliary atresia

Abstract: M2BPGi is a novel fibrosis marker for evaluating the status of the liver in patients with BA, especially when predicting grade F4 fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 22 publications
2
41
0
1
Order By: Relevance
“…Characteristics of these studies are shown in Table 1. 12,14,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] All studies were published between January 2013 and September 2016. The quality of each eligible study, assessed according to the QUADAS-2 criteria, is reported in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of these studies are shown in Table 1. 12,14,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] All studies were published between January 2013 and September 2016. The quality of each eligible study, assessed according to the QUADAS-2 criteria, is reported in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…The cut-off value of WFA + -M2BP for predicting late histological stage was 5.32 in this study. In previous adult studies, the cut-off value for liver cirrhosis was 1.46 in non-alcoholic fatty liver, 15 1.9 in chronic hepatitis B, 24 2.0 in primary biliary cholangitis, 14 3.53 in biliary atresia, 16 and 3.9 in autoimmune hepatitis. 17 Compared to these liver diseases, the cut-off value for of WFA + -M2BP for predicting late histological stage is higher in PSC.…”
Section: Discussionmentioning
confidence: 94%
“…12 Compared with other liver fibrosis serum markers, WFA + -M2BP has been proved to be more useful to identify advanced liver fibrosis and predict the development of hepatocellular carcinoma in adults with chronic hepatitis C. 13 In addition to chronic hepatitis C, recent studies have shown that serum WFA + -M2BP levels are also useful for the prediction of disease progression in chronic hepatitis B, non-alcoholic fatty liver disease, primary biliary cholangitis, biliary atresia, and autoimmune hepatitis (AIH). [14][15][16][17][18] However, the association between liver fibrosis and serum WFA + -M2BP level in PSC remains unknown. If serum WFA + -M2BP levels are useful for assessing the degree of liver fibrosis in pediatric PSC, liver biopsy could be avoided as much as possible in children.…”
mentioning
confidence: 99%
“…Recently, serum Mac‐2 binding protein glycosylation isomer (M2BPGi) was reported as a novel fibrosis marker of chronic liver disease, including hepatitis C virus, hepatitis B virus, non‐alcoholic steatohepatitis, and primary biliary cirrhosis . We have also reported the usefulness of M2BPGi in patients with biliary atresia, suggesting M2BPGi as a less invasive, easy‐to‐use, and high‐quality biomarker with a novel ability to predict the progression of liver fibrosis . In addition, previous studies have demonstrated that M2BPGi not only predicts the status of fibrosis but also has the functional ability to predict the activation of viral hepatitis, recurrence of carcinogenesis, and the risk of post‐hepatectomy liver failure, although the mechanisms underlying this predictive ability are unknown …”
Section: Introductionmentioning
confidence: 98%
“…[6][7][8][9] We have also reported the usefulness of M2BPGi in patients with biliary atresia, suggesting M2BPGi as a less invasive, easy-to-use, and high-quality biomarker with a novel ability to predict the progression of liver fibrosis. 10 In addition, previous studies have demonstrated that M2BPGi not only predicts the status of fibrosis but also has the functional ability to predict the activation of viral hepatitis, recurrence of carcinogenesis, and the risk of posthepatectomy liver failure, although the mechanisms underlying this predictive ability are unknown. [11][12][13][14][15] We, herein, report our attempt to explore the ability of M2BPGi to predict liver graft fibrosis status after LT. To the best of our knowledge, this is the first report to evaluate the ability of M2BPGi to predict liver graft fibrosis after LT. We found that M2BPGi was efficacious for evaluating liver fibrosis in LT recipients.…”
Section: Introductionmentioning
confidence: 99%